Developing Video Tutorial-Based Learning Media to Enhance Users' Understanding of Spada UNS - Ngadimin, Ngadimin; Sakroni, Sakroni; Wahyuningsih, Daru (Universitas Sebelas Maret, 2023)
This study aims to develop video tutorial-based learning media to increase the Online Learning System (Spada) use at Universitas Sebelas Maret, Surakarta. This media development was based on feedback, suggestions, and preliminary survey findings, showing that 24% of the 80 respondents who utilized Spada UNS said there were not enough tutorials for the software. The research method employed was research development (R&D) with development procedures referring to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluations) developed by Dick and Carry. The feasibility of learning media was assessed by media and material experts who were members of the PPTIuP LPPMP UNS peer group. Data collection instruments encompassed questionnaires, literature studies, documentation, and interviews. Data analysis results from the feasibility test then used the Likert scale. On the https://spada.uns.ac.id page, under the